Government & politics of Texas - Halter, Gary M. (McGraw Hill, 2008)
Examining and comparing the Lone Star State to the rest of the nation, this text provides students with a broad understanding of the factors that make Texas unique. The sixth edition includes updated information on a host of issues in Texas state and local government, including population growth, constitutional amendments, and changing partisanship in the Texas legislature. Concise and affordable, Government and Politics of Texas is a perfect supplement for American Government courses or a brief main text for upper-level courses on Texas Politics